Government Role and the Efficiency of Policy Instruments - Tanzi, Vito. (Washington, D.C. : International Monetary Fund, 1995)
Comparisons about the role of the government in an economy are usually made by reference to the share of tax revenue or of public expenditure in gross domestic product. However, governments often use other tools for pursuing their objectives. The paper discusses these other tools, shows the extent to which they can replace the traditional fiscal instruments, and assesses their quantitative importance. Various highly speculative hypotheses are advanced about the role of these other tools in countries at different levels of development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet